(untitled) (Global Journal of Science Frontier Research, 2012)
This study shows strong seasonality of ground level ozone concentrations with spring (September and October) maximum and winter (May and June) minimum levels. The levels were observed in decreasing order per season as: spring>summer>autumn>winter. The Johannesburg ozone levels were much lower than Botsalano and Marikana levels. The monthly levels for the 2007 to 2008 period were determined in order of decreasing abundance as Marikana (21.07 -50.02 ppb), Botsalano (28.17 -37.94 ppb), Buccleuch (2.03 -23.42 ppb), Delta (5.76 -17.32 ppb) and . The precursors of ozone (NO x , NO 2 , and NO) also showed peaks in winter (May-June). Anti-correlation of ozone and its precursors (NO x , NO 2 , and NO) were also observed. The authors also conclude that the formation of ozone in Johannesburg occurs under the VOC-sensitive regime, and that the possible sources of ozone in the city are vehicular and industrial and businesses.